MONEY FOR THE REST OF US : 10 Questions to Master Successful Investing - Stein, J. David (New York : McGrawHill, 2020)
"Learn how to protect and grow your wealth with this commonsense guide to investing You manage your own money. You understand the basics of investing and diversifying your portfolio. Now it's time to invest like a pro for greater profits-with investment expert David Stein, host of the popular weekly podcast, "Money for the Rest of Us." He's created a unique ten-question template that makes it easy for individual investors like you to: Invest more confidently Feel less overwhelmed Build a stronger portfolio Avoid costly mistakes Plan and save for retirement Despite what many people believe, you don't need to be an expert to be a successful investor. With Stein as your personal money mentor, you'll learn how to make smarter, more informed decisions that can help reduce your risk and increase your gains by following a few simple rules for analyzing any investment. This is how the professionals grow their wealth and how you can, too. This is Money for the Rest of Us." -- ONIX annotation.
Includes index
Includes bibliograpgy pages : 217-229
Keywords: Investments; Finance, Personal